INVOLUNTARY CHILDLESSNESS, STIGMA AND WOMEN’S IDENTITY - Grace Stephanie Panggabean (Jurnal Sosiologi Reflektif, 2014)
This article described how to control reproduction and the development of contraception in some case studies: Indonesia, Yunani dan India. The case studies are utilised to illustrate how normative gender roles in the society create stigmatisation of women in involuntary childlessness. They are also used to elaborate how stigma affects women’s construction of identity. The three case studies and other literatures about involuntary childlessness and infertility show how the narrow gendered roles in society affect women negatively.